An analysis of the cultural representation of disability in school textbooks in Iran and England. Issue 1 (2nd January 2018) - Hodkinson, Alan; Ghajarieh, Amir; Salami, Ali
ABSTRACT: The paper details the findings of a study which focused on the analysis of the cultural representation of disability in school textbooks in Iran and England. The paper argues that whilst inclusive education could facilitate the incorporating of disabled pupils into mainstream schools, there needs to be deeper examination as to how this transition should take place for children aged 3–13. The paper suggests that in such examinations, school textbooks might be of significance in familiarising non-disabled pupils, teachers and authorities with the issues related to disability and disabled pupils.